2018
DOI: 10.1590/1980-57642018dn12-020004
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction in Alzheimer’s disease Systematic review and meta-analysis

Abstract: Alzheimer’s disease (AD), a neurodegenerative condition, is one of the most prevalent kinds of dementia, whose frequency doubles for every 5 years of age in elderly.Objective:To determine the correlation between AD and olfactory alterations, identifying the most affected domains and exploring the utility of olfactory tests for complementing early diagnosis.Methods:Databases were searched using the terms “olfactory OR smell OR olfaction AND alzheimer” for articles related to the proposed theme. The selected stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 68 publications
(54 reference statements)
2
40
1
Order By: Relevance
“…Recent studies have established anosmia as a prodromal biomarker for Alzheimer's disease (48)(49)(50) and the presence of olfactory deficits in a subset of MS patients correlating with symptom severity (51,52). GAS-infected mice show severe persistent physiological deficits in M/ T neuronal function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established anosmia as a prodromal biomarker for Alzheimer's disease (48)(49)(50) and the presence of olfactory deficits in a subset of MS patients correlating with symptom severity (51,52). GAS-infected mice show severe persistent physiological deficits in M/ T neuronal function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a meta-analysis 22 showed that olfactory dysfunction occurs in the initial stages of AD and, thus, may be a preclinical indicator of AD. Several studies 23,24 have also shown olfactory impairment associated with spatial memory loss in AD. AD is characterized by excessive accumulation of toxic forms of amyloid-beta (Aβ).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the pathology of impaired CSF flow is one of the pathophysiological mechanisms of brain injury in neurodegenerative diseases. It has been described in olfactory dysfunction as well as in patients with idiopathic intracranial hypertension (IIH), AD and glaucoma …”
Section: Discussionmentioning
confidence: 99%
“…Due to the culture-specific nature of smell perception, the reliability of these tests has to be evaluated in different populations (2) (37). Localized versions of the UPSIT test kit have been introduced in countries such as Brazil (23), Turkey (24), Lithuania (25), and Iran (16) (for an exhaustive review refer to (14)).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the mentioned assessment methods, previous studies have shown that olfactory deficit is an early symptom of Alzheimer’s disease (12) (13). Further studies have demonstrated that standard methods of assessing olfactory system such as sniffing kits can be helpful in distinguishing AD patients from healthy individuals (14) (15) (16).…”
Section: Introductionmentioning
confidence: 99%